Analisis Manajemen Risiko Operasional Pada Bank Syariah Indonesia (BSI) Pasca Merger - Faricha Lita Nabbila; Andriani; Dewi Fatmala Putri; Widya Ratna Sari (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research is motivated by the existence of risks at Bank Syariah Indonesia. Under these conditions, the Bank evaluates and strengthens risk management tools to maintain business quality and the bank's health level. One component of operational risk is the efficiency ratio or what is called the Operational Expenses to Operating Income (BOPO) ratio. The aim of this research is to examine in depth the implementation of operational risk management at BSI which can influence the BOPO ratio at BSI. This research uses a qualitative research approach. The data in this research uses secondary data or literature study. Secondary data obtained came from the official BSI website, books, journals and articles related to research. The data analysis technique used is the Miles and Huberman model of qualitative data analysis techniques. The result of this research is that operational risk management at BSI has been implemented effectively. This is proven by the BSI BOPO ratio from 2021 continuing to decline.